1985
DOI: 10.1139/v85-016
|View full text |Cite
|
Sign up to set email alerts
|

A laser diffraction and nuclear magnetic resonance investigation of the cholesteric potassium N-dodecanoylalaninate mesophase system

Abstract: KEITH RADLEY and ALAN S. TRACEY. Can. J. Chem. 63, 95 (1985). Nematic and twisted nematic mesophases have been prepared from various mixtures of potassium N-dodecanoyl-I-alaninate and its racemate. The induced pitch was determined as a function of optical purity as werc nmr spectra from a variety of additives including several inorganic salts and d,l-alanine. Dipolar couplings from the CHCHl moiety of the alaninate headgroup were studied, as were quadrupole splittings from the N-D of the amido group and the DZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…moiety and is known to form cholesteric mesophases which are composed of micelles (9)(10)(11)(12). However, the structure of in the case of carbon-13 NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…moiety and is known to form cholesteric mesophases which are composed of micelles (9)(10)(11)(12). However, the structure of in the case of carbon-13 NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Heteronuclear broad-band and power-gated proton decoubecome chiral as the content of the L-derivative is increased (12). Enantiomerism in cybotactic systems is also of interest pled carbon-13 NMR spectra, at 30ЊC and 62.95 MHz on a Bruker AM-250 spectrometer, and at ca.…”
Section: Introductionmentioning
confidence: 99%
“…Nematic phase samples can also be obtained by using mixed detergents with oppositely charged head groups. Most quaternary systems can be modified by leaving out the salt resulting in ternary systems which still maintain a nematic phase under a wide range of temperatures and composition variations [9]. The ideal lyotropic amphiphilic nematic phase systems from the theoretical and experimental point of view can be derived from a binary system of detergent and D 2 O only.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Thus Tracey and Diehl discriminated the enantiomers of L L -alanine by 1 H NMR using a sodium n-decylsulfate/())-sodium decyl-2-sulfate/ sodium sulfate/decanol/water system. 10 Later, it was shown that such a discrimination could also be achieved using a potassium N-dodecanoyl-L L -alaninate/decanol/ caesium chloride/water mesophase.…”
Section: Introductionmentioning
confidence: 99%
“…10 Later, it was shown that such a discrimination could also be achieved using a potassium N-dodecanoyl-L L -alaninate/decanol/ caesium chloride/water mesophase. [11][12][13] However, this four component system appeared rather unfriendly to use due to the complexity of the phase diagram and to the instability of the mesophase when dissolving some chiral guest molecules. 14 Recently, Baczko et al reported the synthesis of new sulfonated L L -alanine and L L -phenylalanine surfactant derivatives whose association with some chlorinated Tetrahedron: Asymmetry solvents and water led to liquid crystalline systems.…”
Section: Introductionmentioning
confidence: 99%